Gynecologic Biopsy for Molecular Profiling: A Review for the Interventional Radiologist - Corr, Bradley R.; Behbakht, Kian; Spillman, Monique A. (Seminars in Interventional Radiology, 2013)
The interventional radiologist is often asked to obtain multiple biopsies of gynecological malignancies for genetic profiling. This article reviews the current indications for gynecological biopsy as well as how the information gained contributes to a personalized medicine plan for the individual patient. The specific focus of this review is the current knowledge and practice of molecular profiling for gynecological malignancies.
Keywords: gynecological cancer; interventional radiology; biopsy; genetic profiling; molecular profiling